Contingency and determinism in the evolution of bird song sound frequency - Jakob I. Friis (Nature Portfolio, 2021)
Abstract Sexual signals are archetypes of contingent evolution: hyper-diverse across species, often evolving fast and in unpredictable directions. It is unclear to which extent their evolutionary unpredictability weakens deterministic evolution, or takes place bounded by deterministic patterns of trait evolution. We compared the evolution of sound frequency in sexual signals (advertisement songs) and non-sexual social signals (calls) across > 500 genera of the crown songbird families. Contrary to the acoustic adaptation hypothesis, we found no evidence that forest species used lower sound frequencies in songs or calls. Consistent with contingent evolution in song, we found lower phylogenetic signal for the sound frequency of songs than calls, which suggests faster and less predictable evolution, and found unpredictable direction of evolution in lineages with longer songs, which presumably experience stronger sexual selection on song. Nonetheless, the most important deterministic pattern of sound frequency evolution—its negative association with body size—was stronger in songs than calls. This can be explained by songs being longer-range signals than most calls, and thus using sound frequencies that animals of a given size produce best at high amplitude. Results indicate that sexual selection can increase aspects of evolutionary contingency while strengthening, rather than weakening, deterministic patterns of evolution.